Quantitative parameters of human’s functional state in the ergatic learning environment - Strakhova, Oksana; Ryzhov, Alexey (My University, 2016)
Modern learning process designed for the widespread use of computers and immersive educational environment. A number of papers (see [2], [7]) show the changes in the functional state (FS) of the people working at the computer, which then leads to the persistent violations of the FS. We have considered the possibility of using the integral test - measuring the electroskin characteristics in some micro-zones (ESC MZ) on the human body, in ergatic or immersive computer system to assess its FS. The results showed significant differences in the number of ESC MZ after classes conducted in an ergatic learning environment.
Keywords: functional state; e-learning